Some trends of modern domestic state policy in the field of crime prevention - N. A. Krainova (Правоприменение, 2024)
The subject. The article is devoted to the analysis of current trends in state policy in the field of crime prevention.The author aims to prove that this policy is intuitively focused on prevention and ensuring the security of society and the state from internal and external threats, but needs legislative regulation of the main directions, principles, and approaches.Methodology. Based on the study of legislation and doctrinal sources, the article formulates conclusions regarding the concept of state policy in the field of crime prevention and the need for its conceptualization.Main results. The author focuses on the main trends of modern criminological policy, which include an increase in the number of normative legal acts, primarily of a strategic nature (doctrines, concepts, strategies), which can be attributed with a certain degree of confidence to legislation in the field of crime prevention (criminological).Conclusions. The article argues for the need for balance and strategic vision in this area. The policy in the field of crime prevention should be systematic, thoughtful, balanced, and legislatively defined. In the course of the study, historical, comparative legal, dialectical methods were used, as a result of which the author came to the conclusion about the possibility of regulatory regulation of the conceptual foundations of state policy in the field of crime prevention at the level of a strategic document. The article proposes to develop and adopt at the legislative level the Doctrine of Combating Crime in the Russian Federation, Recommendations on the legal regulation of crime prevention for the CIS member states.